Cardiorespiratory fitness, but not physical activity, is associated with academic achievement in children and adolescents - Tânia Oliveira; Andreia Pizarro; Manuela Costa; Luís Fernandes; Gustavo Silva; Jorge Mota; José Carlos Ribeiro (Taylor & Francis Group, 2017)
Background: Cardiorespiratory fitness (CRF) and physical activity (PA) seem to have positive effects on academic achievement (AA), although in most studies, objective methods of assessment have not been used. Aim: To examine the associations of CRF and PA with AA. Subjects and methods: A sample of 640 youngsters (10-18 years) participated in this cross-sectional study. CRF was estimated with the 20-metre shuttle run test and PA was measured using accelerometers. School grades were used to describe AA using mathematics and native language final grades. The relationship between CRF and PA with AA was analysed using ANCOVA. Results: Results show a significant effect of CRF levels on native language grades, after adjustment for confounders [F(3,414) = 3,99 p < 0.05], but not for mathematics [F(3,360) = 0.95 p > 0.05]. No significant effects of PA levels on AA were found. Conclusions: CRF is associated with moderate-to-vigorous PA (MVPA) and higher levels of CRF may influence AA. CRF is positively correlated with MVPA, suggesting that higher amounts of MVPA might improve CRF and indirectly influence AA. Since CRF is dependent on higher intensities of PA, we can suggest a focus on implementing improvement strategies to increase the intensity of physical education lessons.